Search for techniparticles in e plus jets events at D0 - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Soc, 2007)
We search for the technicolor process p(p) over bar ->rho(T)/omega(T)-> W pi(T) in events containing one electron and two jets, in data corresponding to an integrated luminosity of 390 pb(-1), recorded by the D0 experiment at the Fermilab Tevatron. Technicolor predicts that technipions pi(T) decay dominantly into b(b) over bar, b(c) over bar, or (b) over barc, depending on their charge. In these events b and c quarks are identified by their secondary decay vertices within jets. Two analysis methods based on topological variables are presented. Since no excess above the standard model prediction was found, the result is presented as an exclusion in the pi(T) vs rho(T) mass plane for a given set of model parameters.